12 Experimental study on the effect of Perilla seed in the rat model of asthma. (19th December 2016) - Li, Yan; Wang, Tang; Yu, Tao; Xi, Peng; Miao, Mingsan
Abstract : Objectives: To investigate the effects of Perilla seed in the rat model of bronchial asthma. Methods: To observe the effect of ovalbumin (OVA) on the behavior of rats, NO and IL-6 levels in serum and in the lungs were measured using aluminium hydroxide sensitisation and an OVA aerosol inhalation challenge. Histopathological changes were examined to study the effects of Perilla consumption. Results: The rat model of bronchial asthma was successfully established. Compared with model group, large, medium and small doses of Perilla seed significantly increased the weight of bronchial asthma rats ( p < 0.01) and significantly decreased serum levels of NO and IL-6 ( p < 0.01). Conclusions: Perilla frutescens seed has a protective effect in the rat model of bronchial asthma. Acknowledgments: The study was financially supported by the Collaborative Innovation Centre for Respiratory Disease Diagnosis and Treatment and Chinese Development of Henan Province National Natural Science Foundation of China (Grant No. XTZX2015023).